Assessment of the conceivable inhibitory activity of pathogenic microorganisms extracted from seaweed using phytochemicals, antioxidants, and in-silico molecular dynamic simulation - Eman A. Alwaleed; Nahaa M. Alotaibi; Abdallah Tegeldein Mansour; Mashaill A. Alghamdi; Asmaa S. Abdelgaliel (Scientific Reports)
Abstract Turbinaria ornata, Polycladia myrica, and Padina pavonica is a perennial Mediterranean-native seaweed that is commonly used for mass display. The principal aims of this reconnaissance were the isolation of various compounds from methanolic seaweeds extraction and screening the potential effect as antibacterial, and antioxidant. The micro-dilution method was used to measure antibacterial activity. Gas chromatography-mass spectrophotometry (GC. Mass) abused to analyze the chemical components of the methanolic seaweed extract. The existence of 19 secondary metabolites was discovered using GC–MS analysis: 8 different compounds for each seaweed's species. Among these bioactive compounds, 4 compounds from P. pavonica extract showed the binding affinity and ability to react with Beta-ketoacyl synthase (PDB ID 1EK4) of Escherichia coli. The phytocompounds' drug-like and poisonous characteristics were predicted. Auto Dock was used to examine the ligand receptor complexes' binding strength. T. ornate and P. pavonica had the highest activity against K. pneumonia, with 22.50 mm (0.78 µg/ml) and 22.23 mm (5.10 µg/ml) obtained, respectively. In a concentration-dependent manner, the extract components demonstrated substantial antioxidant activity. P. pavonica had the highest scavenging activity (78.00%, IC50 = 6.35 µg/ml), while ascorbic acid had a 96.45% scavenging impact. Because the chemicals bind to the Lipinski Ro5, they have drug-like characteristics. The compounds had no hepatotoxic effects. P. pavonica extract has the prospect of being used as a source of medicinal drug-like chemicals. The docking investigation found a strong correlation between the experimental results and the docking results. Finally, brown seaweed extract, particularly P. pavonica extract, demonstrated strong antibacterial, antioxidant, and free radical scavenging properties.